ANALISIS PENERIMAAN PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH SEBELUM DAN SETELAH ADANYA PANDEMI COVID-19 DI KABUPATEN DAN KOTA SE-JAWA TENGAH - Anisa Arifiyanti; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2022)
The study aimed to find out the realization of local tax revenues in districts and cities at Central Java during Covid-19 pandemic and its contribution to original local government revenue period of 2019-2020. Furthermore, the variables used in this study were the district and city taxes including taxes for hotel, restaurant, entertainment, billboard, street lighting, non-metallic mineral as well as rock, parking, underground water, swallow nest, land and building, and acquisition duty of right on land and building. All districts and cities at Central Java were the population and sample used in this study. In addition, the sampling method used was saturated sample. The total research sample was 70 consisting of 29 districts and 6 cities that reported the realization of local tax revenues period of 2019-2020. Besides, hypothesis testing with comparative method used Wilcoxon Signed Rank Test. The result of Wilcoxon Signed Rank Test indicates that the decrease occurs on tax revenues of hotel, restaurant, entertainment, street lighting, parking, non-metallic mineral as well as rock during Covid-19 pandemic. Meanwhile, tax revenues of billboard, underground water, swallow nest, land and building, and acquisition duty of right on land and building increases during Covid-19 pandemic. Besides, the average of contribution level is at the moderate level.